2020
DOI: 10.3390/ijerph17030959
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Age, Sex and Smoking Habit on Flavor Recognition in Healthy Population

Abstract: (1) Background: Flavor is one of the main factors influencing food preferences and dietary choices, and a reduction in flavor recognition has been associated with several diseases. A novel quantitative test to assess flavor has been recently developed and validated. The aim of the present work was to define the standard of flavor recognition in the general healthy population. (2) Methods: Three hundred and forty-eight healthy volunteers (18–80 years) performed the flavor test (FT). The test consisted of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…Our findings do not support previous studies that have demonstrated women outperform men on orthonasal olfactory tests and that olfactory ability declines with age 13,19 . Moreover, previous studies have shown that retronasal olfactory function also declines with age 8,20,21 . However, our findings are consistent with two previous studies that found retronasal olfaction was not affected by age 9,21 .…”
Section: Discussioncontrasting
confidence: 98%
“…Our findings do not support previous studies that have demonstrated women outperform men on orthonasal olfactory tests and that olfactory ability declines with age 13,19 . Moreover, previous studies have shown that retronasal olfactory function also declines with age 8,20,21 . However, our findings are consistent with two previous studies that found retronasal olfaction was not affected by age 9,21 .…”
Section: Discussioncontrasting
confidence: 98%
“…Six clinical studies with measured olfaction showed an association between smoking and OD, with one additional study finding significant smoking‐OD associations only in patients with posttraumatic OD (PTOD) 1093–1099 …”
Section: Pathophysiologymentioning
confidence: 99%
“…Despite reported differences in gender taste responsiveness (Williams et al, 2016), neither smell or taste sensitivities were found. The effects of smoking habits on taste or flavor are controversial (Nettore et al, 2020). These authors, with a cohort of 83 smokers among 348 subjects, reported that flavor recognition was not affected by cigarette smoking.…”
Section: Influence Of Taster Categories On Aroma and Flavormentioning
confidence: 99%